Studi Estimasi Beban Puncak Hari Libur Nasional Sistem Interkoneksi Sulselbar Menggunakan Jaringan Syaraf Tiruan Propagasi Balik - Makmur Saini; A.M. Shiddiq Yunus; Firdaus Firdaus (Jurnal Teknik Mesin Sinergi, 2020)
The development of population from time to time is increased and the need for electricity consumption is also increased. Simultaneously increasing the need for electric power requires the provider of electricity supply in this case PT. PLN (Persero) should deliver power effectively to consumers. To maximize the distribution of electricity to the consumer, a load planning is required. This load planning is conducted to find out how much amount of power is required by consumer. The purpose of this research is to investigate the need of power load of interconnection system of South Sulawesi and to investigate the accuracy of load planning using Artificial Neural Network (ANN) backpropagation.